The synthesis and characterisation of metal complexes containing chemically reduced bipyridyl ligand systems - Irwin, M (2013)
This thesis describes the synthesis and characterisation of metal complexes that contain chemically reduced bipyridyl ligands. The crystal structures of twenty-six novel complexes are reported alongside detailed discussions on the electronic and spectroscopic effects and trends associated with the different oxidation states within these species. Chapter One introduces the isomers of bipyridine and their redox chemistry, the concept of non-innocent ligands and the spectroscopic techniques that are currently used in determining ligand oxidation states. Subsequently, examples of main group, transition metal, lanthanide and actinide species that contain or may contain reduced forms of the ligand are discussed. Chapter Two details the synthesis and structural characterisation of alkali metal salts of singly and doubly reduced forms of the three commercially available bipyridine isomers. The effects of this reduction are investigated with the aim of developing diagnostic fingerprints for each of the ligand oxidation states. Chapter Three discusses the synthesis of an homologous series of compounds of the form [M(2,2'-bipy)(mes)2]n– where M = Cr, Mn, Fe, Co, Ni and n = 0, 1. Trends in magnetism, bonding and electronic structure are investigated with reference to theoretical calculations and the diagnostic fingerprints identified in the previous chapter. Chapter Four describes the synthesis and characterisation of three compounds containing the isostructural motif [Zn2(4,4'-bipy)(mes)4]n– where n = 0, 1, 2. Structural and spectroscopic changes are discussed and com- pared to theoretical calculations. Chapter Five contains descriptions of the spectroscopic techniques employed in the above research and synthesis routes to all compounds featured in this thesis.